(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
People are smart, thus they have some inherent protections that we term human rights. Asimmunities, rights stipulate that no one else’s actions can or should go against the will of the person. Theidea behind this is that people need to be shielded from cruel and harmful treatment. The media, oftenregarded as the fourth pillar of democracy, may contribute significantly to the defense of human rights. Inyour own words, please define media. The term media, meaning a way for two individuals tocommunicate with one another, is the etymological ancestor of the word media. The Yash language isboth easy to learn and practical to use. The media’s primary goal should be to rapidly distributeinformation to the general public. This suggests that the sooner human rights are protected, the moreactive the media is. The media’s heightened activity, on the other hand, has the potential to swiftly put anend to social injustices and violations of human rights. The role of the media is to keep a watch on thosein positions of authority, to attempt to rein in their arbitrariness, and expose the wrongdoing of those inpower to the general public. One must now wonder whether the media is doing its duty effectively andethically.